Is there a role for public support of incumbent worker on-the-job training? - Kevin Hollenbeck (W.E. Upjohn Institute for Employment Research, 2008)
States have begun to use training subsidies as a policy tool for employment retention and business competitiveness. This paper summarizes a survey of states concerning their investments in incumbent worker training. Altogether, states are investing about 550 to 800 million, which is perhaps one percent or less of total private sector training costs. The paper further discusses a study conducted for one state in which we found significant fiscal returns implying that underinvestment of public funds for incumbent worker training may be occurring. In this state, primary sector jobs were created or retained at a public cost of less than 9,000 per job; a cost that rivals or bests most economic development initiatives.
Keywords: J24; J28; I28; 330